Pengaruh Penggunaan Gadget Terhadap Pola Interaksi Sosial Siswa SMA di Kecamatan Langke Rembong - Jamun, Yohannes Marryono; Ngalu, Rudolof; Wejang, Heronimus Emilianus Arjono (JIPD (Jurnal Inovasi Pendidikan Dasar), 2019)
The research is motivated by the use of gadgets, especially smartphones, which are increasingly popular among teenagers, especially high school students in Ruteng city. Using qualitative-descriptive research is considered suitable for smartphone use problems and their impact on social interaction. The Conclusion is (1) the use of smartphones has a positive impact, the presence of smartphones helps facilitating students to interact, the presence of smartphones makes the spectrum of communication or social interaction of students expanded; (2) the negative impact of smartphone use, declining quality of communication and direct face-to-face interaction; (3) in relation to school, smartphones make it easier for students to interact with their peers such as discussing certain assignments or subject matter. Space and time barriers can be overcome by interaction through social media such as WhatsApp and Facebook. (4) Excessive use of smartphones also negatively affects students learning. As admitted by students themselves that the functions offered by smartphones often make students complacent and ignore their responsibilities in learning and completing school assignments.